Synthesis of Mesoporous Carbon from Merbau Sawdust as a Nickel Metal Catalyst Support for Castor Oil Hydrocracking - Wega Trisunaryanti; Triyono Triyono; Suryo Purwono; Aprilia Siti Purwanti; Satriyo Dibyo Sumbogo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Synthesis of mesoporous carbon from merbau sawdust with H2O2 as activator using reflux method followed by carbonization at 800 °C (RC800) had been carried out. This research is aiming to produce effective pathway to synthesize effective nickel-mesoporous carbon catalyst. The nickel metal was impregnated on the mesoporous carbon by wet impregnation using the salt precursor of Ni(NO3)2∙6H2O. The results showed that carbon RC800 and C800 had a specific surface area of 135.18 and 182.48 m2/g. Specific surface area of Ni/RC800 and Ni/C800 catalyst were 41.31 and 7.15 m2/g, respectively. The metal content in Ni/RC800 and Ni/C800 catalyst were 0.83 and 0.92 wt%, respectively. Ni/RC800 catalyst had the highest acidity (7.64 mmol/g) compared to Ni/C800 catalyst (6.99 mmol/g), RC800 (97.43 mmol/g), and C800 (6.17 mmol/g). The Ni/RC800 catalyst has the highest activity with the liquid product conversion of 66.01 wt%. Its selectivity towards gasoline fraction, diesel fraction, alcohol, and organic was 8.06, 1.17, 2.61, and 54.13%, respectively. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).